Private Sector Provision as an “Escape Valve”: The Mexico Diabetes Experiment - Bronsoler, Ari; Gruber, Jonathan; Seira, Enrique (Review of Economic Studies, 2025)
Abstract Public health systems are dominant in much of the world but often face fiscal constraints that lead to rationing of care. As a result, private sector healthcare providers could in theory beneficially supplement public systems, but evaluating the benefits of private alternatives has been challenging. We evaluate a private supplement to the free public health system for one of the world’s deadliest health problems, diabetes. We estimate enormous impacts of the private supplement, increasing the share of those treated who are under control by 69%. This effect arises through both improved treatment compliance and health behavior. We find diabetes complications fall in the short run, and that the net costs of this intervention are one-third of the gross costs. The returns to private care do not appear to reflect more productive delivery but rather more attachment to medical care, offering lessons for improving the public system.